1984
DOI: 10.1152/jappl.1984.57.6.1662
|View full text |Cite
|
Sign up to set email alerts
|

Effect of central hypervolemia on cardiac performance during exercise

Abstract: To investigate the effect of different levels of central blood volume on cardiac performance during exercise, M-mode echocardiography was utilized to determine left ventricular size and performance during cycling exercise in the upright posture (UP), supine posture (SP), and head-out water immersion (WI). At submaximal work loads requiring a mean O2 consumption (Vo2) of 1.2 1/min and 1.5 1/min, mean left ventricular end-diastolic and end-systolic dimensions were significantly greater (P less than 0.05) with WI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
25

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 0 publications
5
35
0
25
Order By: Relevance
“…• O 2 is variable and depends on exercise intensity (Sheldahl et al, 1984(Sheldahl et al, , 1987Connelly et al, 1990;Cureton, 1997), exercise mode (Cureton, 1997), water depth (Gleim and Nicholas, 1989;Cureton, 1997) and water temperature (Craig and Dvorak, 1969;McArdle et al, 1976;Gleim and Nicholas, 1989;Cureton, 1997;Hall et al, 1998;Shimizu et al, 1998). In the present study, the relationship between HR and V • O 2 during waterwalking, with a water temperature of 30°C and water depth at the level of the xiphoid process, was similar to that during land-walking.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…• O 2 is variable and depends on exercise intensity (Sheldahl et al, 1984(Sheldahl et al, , 1987Connelly et al, 1990;Cureton, 1997), exercise mode (Cureton, 1997), water depth (Gleim and Nicholas, 1989;Cureton, 1997) and water temperature (Craig and Dvorak, 1969;McArdle et al, 1976;Gleim and Nicholas, 1989;Cureton, 1997;Hall et al, 1998;Shimizu et al, 1998). In the present study, the relationship between HR and V • O 2 during waterwalking, with a water temperature of 30°C and water depth at the level of the xiphoid process, was similar to that during land-walking.…”
Section: Discussionsupporting
confidence: 67%
“…Sheldahl et al (1984) reported that although mean heart rate in water and on land at rest and at the same level of V • O 2 during moderate exercise was similar, during heavy exercise mean HR was lower in water. The water temperature in the latter study was 31.0 ± 0.5°C.…”
Section: Discussionmentioning
confidence: 94%
“…Com a leitura dos trabalhos, observou-se que a mudança da posição corporal também vem sendo considerada um dos fatores que ifluenciam a variável em questão (11,17).…”
Section: Mareriais E Métodosunclassified
“…Sheldahl et al (17) não encontraram diferenças ao observar as respostas de FCr em homens nas posições de decúbito dorsal e otostática no ambiente terrestre e aquático (31 C). Kruel et al (11) analisaram as respostas da FCr de homens imersos na posição ortostática até a profundidade da cicatriz umbilical, em temperatura de 30 C, comparando com as posições decúbito dorsal e ortostática fora da água.…”
Section: Mareriais E Métodosunclassified
“…The physical properties of water change hemodynamic and metabolic responses: stroke volume increases by 30-50% and cardiac output at a given work load also increases about 25% through the Frank Starling mechanism. 15,16 From increased cardiac output as a result of increased cardiac filling pressure and lowered total peripheral resistance 17 it can be assumed that O 2 extraction in working muscles is more efficient in W than on L. However at present the effect is discussed controversial. Blood flow to oxidative muscles can also be affected if muscle pump generates a greater pressure gradient across the capillary bed and increases blood flow.…”
Section: Introductionmentioning
confidence: 99%